Examining the Impact of Accounting Practices on Socioeconomic Growth and Equity - Muslim, Muslim (Advances in Applied Accounting Research, 2023)
Purpose: The research investigates the impact of accounting practices on socioeconomic growth and equity, aiming to elucidate the complex relationship between these practices and societal outcomes. Research Design and Methodology: A qualitative approach was adopted, with a systematic review of literature from databases such as PubMed, Google Scholar, and Web of Science. The study focused on keywords such as "accounting practices," "socioeconomic growth," and "equity," employing thematic analysis to identify patterns and themes within the data. Findings and Discussion: The findings suggest that transparent financial reporting and robust accounting standards are crucial in driving economic development and promoting social equity. The adoption of environmental, social, and governance (ESG) criteria in financial reporting has also become increasingly significant, contributing to more inclusive growth and sustainable development. Implications: This study highlights the crucial role of accounting practices in shaping socioeconomic outcomes. It calls for evidence-based policy interventions and corporate practices that emphasize equity and sustainability, thereby fostering more inclusive socioeconomic development.